2012
DOI: 10.1172/jci58620
|View full text |Cite
|
Sign up to set email alerts
|

CBX7 is a tumor suppressor in mice and humans

Abstract: The CBX7 gene encodes a polycomb group protein that is known to be downregulated in many types of human cancers, although the role of this protein in carcinogenesis remains unclear. To shed light on this issue, we generated mice null for Cbx7. Mouse embryonic fibroblasts derived from these mice had a higher growth rate and reduced susceptibility to senescence compared with their WT counterparts. This was associated with upregulated expression of multiple cell cycle components, including cyclin E, which is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
163
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 44 publications
8
163
0
1
Order By: Relevance
“…This suggests that the Thr-118 phosphorylation motif holds important function and will be interesting to examine further in the context of cancer, particularly those tumors driven by ERK signaling, such as melanoma. To date, CBX7 has been implicated as an oncogene in prostate cancer and lymphoma, as well as a tumor suppressor in lung and breast cancer (17,18,58,59). Consistent with this, we noted a loss of Cbx7 expression (and T118ph) in a series of mouse mammary carcinoma cells with increasing metastatic ability.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that the Thr-118 phosphorylation motif holds important function and will be interesting to examine further in the context of cancer, particularly those tumors driven by ERK signaling, such as melanoma. To date, CBX7 has been implicated as an oncogene in prostate cancer and lymphoma, as well as a tumor suppressor in lung and breast cancer (17,18,58,59). Consistent with this, we noted a loss of Cbx7 expression (and T118ph) in a series of mouse mammary carcinoma cells with increasing metastatic ability.…”
Section: Discussionsupporting
confidence: 87%
“…Both CBX6 and CBX7 have been suggested to play an oncosuppressive role in solid tumors [24] and, as shown in the Oncomine database, in myeloid leukemias (Figure 3). Notably, CBX7 oncosuppressive activity is predominant in hematologic neoplasms [25]. Taken together, this evidence suggests that CBX6 and CBX7 could play a tumor suppressive role in CML also, and that their concurrent activation upon imatinib treatment might lead to the silencing of prosurvival genes, thereby inducing neoplastic cell death and better short-term responses to imatinib.…”
Section: Discussionmentioning
confidence: 83%
“…CBX7, as a reader protein, plays an important role in promoting the recruitment of polycomb repressive complex (PRC)-1 to the target chromatin by recognizing PRC-2-mediated H3K27me3 (2). Moreover, CBX7 regulates gene expression by altering histone acetylation and DNA methylation (3)(4)(5)(6). Recent studies have suggested that CBX7 regulates the balance between self-renewal and differentiation in embryonic stem cells (ESCs) and hematopoietic stem cells (HSCs) (7)(8)(9).…”
Section: /Esamentioning
confidence: 99%